Analysis of the Relationships Between Economic Growth and Income Distribution in West Java - Larasati, Devina Ayudia; Santoso , Dwi Budi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to determine what factors affect economic growth and prove whether economic growth has been accompanied by income equality in West Java Province in 2010-2022. This study uses secondary data in the form of economic growth rate data, Gini ratio index data, average years of schooling data life expectancy data, Domestic Investment (PMDN) and Foreign Investment (PMA) data in West Java province obtained from the Central Bureau of Statistics (BPS) of West Java Province and Open Data Jabar. This research method uses simultaneous panel data regression analysis (2SLS). The findings of this study resulted in two equations. For the first equation, partially education has a positive and significant effect, PMDN and PMA show an insignificant positive effect on economic growth. For the second equation, economic growth partially has a significant positive effect on income inequality.